Sustained maintenance of clinical remission after adalimumab dose reduction in patients with early psoriatic arthritis: a long-term follow-up study - Cantini F (Dove Medical Press, 2012)
Fabrizio Cantini, Laura Niccoli, Emanuele Cassarà, Olga Kaloudi, Carlotta NanniniDivision of Rheumatology, Misericordia e Dolce Hospital of Prato, Prato, ItalyPurpose: The primary purpose of this study was to evaluate the proportion of psoriatic arthritis (PsA) patients maintaining clinical remission after adalimumab (ADA) dose reduction compared with patients with rheumatoid arthritis. Secondary purposes include evaluating the proportion of PsA patients who achieve remission, the duration of remission after ADA dose reduction, time to relapse, psoriasis course, and the frequency of adverse events at the end of follow-up.Methods: This was a single-center, prospective, follow-up, case-control study of 76 consecutive patients (35 females, 41 males; mean age 46 ± 10.2 years) who met the classification criteria for psoriatic arthritis and required anti-tumor necrosis factor therapy according to Group for Research and Assessment of Psoriasis and Psoriatic Arthritis recommendations. The 76 patients were compared with 55 patients (40 females, 15 males; mean age 50 ± 11.6 years) who satisfied the American College of Rheumatology criteria for rheumatoid arthritis and received the same treatment. Case patients and controls were recruited from January 2008 to December 2010. At baseline, PsA patients and controls received 40 mg of ADA every other week, usually with methotrexate (10 to 20 mg/weekly). In the presence of clinical remission, ADA dose was reduced to 40 mg every 4 weeks in both groups.Results: Fifty-three of the 76 (69.7%) PsA patients and 17 of the 55 (30.9%) rheumatoid arthritis (P < 0.019) controls achieved remission after a mean time of 5.1 ± 1.2 and 6.3 ± 1.6 months, respectively (P = nonsignificant). After halving the dose of ADA, 47 of the 53 (88.6%) PsA patients and three of the 17 (17.6%) controls maintained remission (P = 0.016) over a mean follow-up period of 28.9 ± 8.4 and 24.2 ± 6.4 months, respectively. No significant changes in Psoriatic Arthritis Severity Index scores were observed. The mean time to relapse was 8.3 ± 3.4 months in six case patients and 7.2 ± 4.2 in 14 controls (P = not significant). No serious adverse events occurred in either group.Conclusion: Clinical remission is possible in a high percentage of patients with early PsA receiving ADA. Such remission is maintained in a high proportion of subjects after ADA dose halving, with relevant advantages in terms of patient compliance, drug-exposure risk, and economic burden.Keywords: psoriatic arthritis, anti-TNF, adalimumab, remission, dose reduction